DIAGNOSTICS AERODYNAMIC OF AIRCRAFT IN THE PROCESS OF EXPLOITATION - Казак, В.; Шевчук, Д. (Science-based technologies, 2011)
The mathematical model of authentication of sudden damages of the outside of the airplane  is offered, which al-lows at the known descriptions and problem spaces in the process of flying exploitation to define probability of stay  the  airplane.  It  is offered  the  block  diagramme  of  the  automated  monitoring and  diagnostic  system  of  an aerodynamic condition of the airplane while in service and reorganisation control to them in special situations